Analisis Mutu Air Tanah Dangkal di Sekitar Kegiatan Pengeboran Minyak Bumi PT Pertamina Hulu Energi (PHE) Jambi Merang - Siti Umi Kalsum; Marhadi Marhadi; Yahya Erwin Rio Saputra (Jurnal Ilmiah Universitas Batanghari Jambi, 2026)
This study aims to evaluate the quality of shallow groundwater based on iron (Fe) and manganese (Mn) parameters, as well as analyze the spatial distribution pattern of pollutants in the area around PT Pertamina Hulu Energi (PHE) Jambi Merang's petroleum drilling activities. Sampling was carried out at eight points of dug wells, including one company-owned monitoring well, three wells located within a radius of ±2 km the drilling site, and four wells located in community residential areas up to a radius of ±9 km. Water quality analysis is carried out through laboratory testing with reference to water quality standards for hygiene and sanitation purposes in accordance with the Minister of Health Regulation Number 2 of 2023. Furthermore, spatial distribution modeling was carried out using the Inverse Distance Weighting (IDW) and Krigging interpolation methods. The results showed that at some observation points, the concentrations of iron (Fe) and manganese (Mn) were detected to exceed the set quality standard values, with a tendency to higher concentrations in wells located closer to the drilling area. The spatial distribution pattern indicates a decrease in metal concentrations as the distance from the source of the pollutant increases. These findings emphasize the importance of regular groundwater quality monitoring and the implementation of sustainable environmental management to protect the availability of water sources for the community.